(untitled) (Journal of Libya for geographical studies, 2024)
The study aims to know the dangers of the wadi Leptis floods on The ancient city of lepta’s located about3km, east of the city of alkhoms, as it is one of the three ancient cities of lepta’s magna, oia, and sobratah, which constited a cultural heritage and a significant economic resource, bypre preparing adata base on the morphometric characteristics of the wadi Leptis basin using… geographic information systems (GIS) software.to understand the reasons floods and presenting them to those challenging the decision to develop appropria strategies to avoid their dangers to the city’s archaeological landmarks.Tochiave the objectives of the research, we relied on the quantitative or mathematical (morphometric)approach to make measurements related to the dimensions of the basin and its drainage network ,the descriptive analytical approach, and the historical approach, and presenting the history of the to which the ancient city was exposed throughout history the extent of the possibility of their recurrence in the future, and conducting number of land marks, and presenting the results of the decision to develop appropria strategies to avoid their dangers to the city’s archaeological landmarks of the research concluded with asset of results, the most important of which are the type of morphometric characteristics of the valley, and the closeness of the shape of its basin to atriangular shape which increased the Frequency f of floods which pose a threat to the monuments of the nearby archaeological city located on both sides of the valley and the tip of itsmouth,in addition to the features most depicted by the floods in the area in the eastern and central mountains and the best north -east of the city, with green degrees reaching120 ut of 15 degrees, and this is what you are on the ABC scale of fraud and risk.